On application of Cramer’s rule - Apynis, Antanas (Lietuvos matematikos rinkinys, 2011)
The article analyses a possibility of modification of Cramer’s rule. The modified formulas for the solution of a system of linear equations, with application of which the volume of calculation reduces,are suggested.
Keywords: system of linear equations; matrix; determinant; linear combination of equations; Cramer’s rule; solution